The Game of Social Life: An Assessment of a Multidimensional Poverty Simulation - Bramesfeld, Kosha; Good, Arla (TRAILS: Teaching Resources and Innovations Library for Sociology, 2015)
This article presents the development of a new simulation activity, the Game of Social Life. The activity introduces students to concepts of social stratification based on multiple dimensions of poverty, including inequalities related to housing, education, occupational status, social power, and health outcomes. The game was administered to students enrolled in a social psychology course at a small, private, liberal arts university located in the midwestern United States. Qualitative analysis of 25 students’ written reactions revealed that the game was engaging and successful in motivating students to adopt a new perspective, acknowledge inequality and explanations for poverty, self-reflect about privilege and oppression, and consider solutions to these problems. The activity was also assessed as a training exercise with 16 staff members at a nonprofit agency located in an urban area in southeastern Canada. These assessments indicate that the activity can be used in a variety of contexts.